Effect of draught conditions and ignition technique on combustion performance of firewood roomheaters. (May 2017) - Reichert, G.; Hartmann, H.; Haslinger, W.; Oehler, H.; Mack, R.; Schmidl, C.; Schön, C.; Schwabl, M.; Stressler, H.; Sturmlechner, R.; Hochenauer, C.
Abstract: Firewood roomheaters are popular, widespread and important for reaching European CO2 emission targets. Since they contribute significantly to local air pollution, they have to be optimized towards minimal emission release, especially in real-life operation. Draught conditions and user behavior, particularly the ignition technique, significantly affect the emission and efficiency performance of firewood roomheaters. This study assessed the effects of the respective parameters experimentally. The results revealed a clear correlation between draught conditions and thermal efficiency. Increased draught conditions up to 48 Pa significantly decreased thermal efficiency by 6%–11% absolutely. However, for gaseous emissions no clear trend was observed. Accordingly, CO and OGC emissions increased at higher draught conditions for one tested roomheater by 30% and 60%, but decreased for two other tested roomheaters by 13%–45%. For PM emissions no effect of increased draught conditions was evident. Top-down ignition technique did not lead to a significant decrease of PM emissions compared to bottom-up ignition. In contrast, bottom-up ignition led to best thermal efficiencies. The use of either spruce or beech as kindling material revealed no significant relevance for the ignition performance. Highlights: Comparative assessment of top-down and bottom-up ignition technique. Effect of ignition technique on CO, OGC and PM emissions of starting batch. Impact of different kindling material on ignition performance. Effect of draught conditions on CO, OGC and PM emissions and thermal efficiency.